2013
DOI: 10.1177/1934578x1300801127
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect ofBroussonetia papyriferaandLonicera japonicain Ovalbumin-induced Murine Asthma Model

Abstract: Broussonetia papyrifera (L.) Vent. and Lonicera japonica Thunb. have been used in recent medicinal research for their antioxidative and anti-inflammatory properties. The present study investigated the therapeutic efficacy of B. papyrifera and L. japonica ethanolic extracts in a murine model of ovalbumin-induced asthma, in which intra-peritoneal (IP) injections and aerosol ovalbumin delivery were used to induce allergic asthma. Bronchioalveolar lavage fluid (BALF), serum samples, lungs and livers were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
1
9
0
2
Order By: Relevance
“…Therefore, LJF and LF act synergistically on the NF-κB signalling pathway but under different mechanisms. LJF has a considerable effect on ovalbumin-induced asthma in a rat model [32]. By contrast, research on LF is few and there is no study has directly demonstrated that whether the LF have an proportional effect on asthma or not.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, LJF and LF act synergistically on the NF-κB signalling pathway but under different mechanisms. LJF has a considerable effect on ovalbumin-induced asthma in a rat model [32]. By contrast, research on LF is few and there is no study has directly demonstrated that whether the LF have an proportional effect on asthma or not.…”
Section: Discussionmentioning
confidence: 93%
“…The water extracts of Lonicerae japonicae flos have significant anti-inflammatory effects on classical inflammatory models such as carrageenan/formaldehyde-induced rat paw swelling [ 50 ], mouse ear edema [ 13 , 51 ], cotton ball granulomatous hyperplasia, mouse cutaneous vascular hyperpermeability [ 52 ], and egg white-induced localized acute inflammation [ 53 ]. Furthermore, it also exhibits anti-inflammatory effect in rat cervicitis model [ 54 , 55 ], Escherichia coli -infected mouse model [ 56 ], excision wound model of infected rat [ 57 ], and ovalbumin-induced rat asthma model [ 58 ]. The mechanisms include inhibition of inflammatory factor synthesis/release, decreased expression of immune related molecules, and enzyme activities of matrix metalloproteinase.…”
Section: Modern Pharmacological Studies On Lonicerae Japonicae Flomentioning
confidence: 99%
“…Antioxidant activities have been described for related polyphenolic constituents extracted from the stem, bark and wood of B. papyrifera ( Xu et al, 2010 ). There is report about the radix of B. papyrifera that had the greatest antinociceptive and anti-inflammatory effects when different parts of the plant were compared as treatment for chemical-induced pain and inflammation in rodents ( Hong et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%